Propagacion rapida de la yuca - Cock, James H. (International Center for Tropical Agriculture, 1979)
A system for rapid propagation of cassava is described, including detailed characteristics of the installations (propagation chambers and rooting area), materials needed and process to be followed. The advantages of this system are: (1) it is the only way of rapidly propagating promissory var. in sufficient quantities; (2) var. affected by CBB (Xanthomonas manihotis) can be cleaned, and (3) it is a simple, inexpensive system. When comparing this system with the traditional one, a greater than no. of commercial-sized cuttings were obtained (100- 400 vs. 12,000-24,000 cuttings/yr). (CIAT)